Rekonstruksi Hadits dan Konsep Doublemovement (Telaah Pemikiran Fazlur Rahman sebagai Pembacaan Hadits Kontemporer) - Rajendra Rahmat Ramadhan (Universitas Pahlawan Tuanku Tambusai, 2023)
The study of al-Hadith has been developed by earlier scholars, but over time, thoughts on Hadith have evolved. Fazlur Rahman offered his theory regarding the reconstruction of understanding Hadith, such as the Double Movement. The Double Movement represents his